Extended Emission-line Region in a Poststarburst Galaxy Hosting Tidal Disruption Event AT2019qiz and Quasiperiodic Eruptions - Yifei Xiong; Ning Jiang; Zhen Pan; Lei Hao; Zhenzhen Li (The Astrophysical Journal, 2025)
We present a comprehensive analysis of the extended emission-line region (EELR) in the host galaxy of the tidal disruption event (TDE) AT2019qiz, utilizing Very Large Telescope (VLT)/MUSE integral-field spectroscopy. The high spatial-resolution data reveal a biconical emission structure approximately 3.7 kpc in scale within the galactic center, characterized by a prominent [O iii ] line in the nucleus and significant [N ii ] line emission extending into the EELR. Spectral analysis of the EELR indicates line ratios consistent with Seyfert ionization in the center and LINER-type ionization in the outer diffuse region, suggesting ionization from galactic nuclear activity. The required ionizing luminosity, estimated from the H α and H β luminosities based on the photoionization and recombination balance assumption, is 10 ^41.8 erg s ^−1 for all spaxels classified as active galactic nucleus (AGN), and 10 ^40.7 erg s ^−1 for spaxels in the central 0.9 kpc Seyfert region. However, the current bolometric luminosity of the nucleus L _bol ≤ 10 ^40.8 erg s ^−1 , estimated from quiescent-state soft X-ray observations, is insufficient to ionize the entire EELR, implying a recently faded AGN or a delayed response to historical activity. Stellar population analysis reveals a poststarburst characteristic in the EELR, and the gas kinematics show disturbances and noncircular components compared to the stellar kinematics. Notably, the recent detection of quasiperiodic eruptions (QPEs) in the X-ray light curve of AT2019qiz confirms the TDE–QPE association. Our findings provide direct evidence for an AGN-like EELR in the host galaxy of the nearest TDE with QPE detection, offering new insights into the complex interplay between TDEs, QPEs, AGN activity, and host-galaxy evolution.